A Novel MAC Scheme for Reliable Safety Messages Dissemination in Vehicular Networks - Alam, Muhammad (2020)
Safety messages dissemination in vehicular networks requires real-time and deterministic medium access. The existing standard, IEEE 802.11p, for vehicular networks is based on Carrier Sense Multiple Access (CSMA) which is not a deterministic mechanism as collision may occur to access the medium that can cause unbounded delays. Therefore, in this paper, we presented a new deterministic Medium Access Control (MAC) scheme for vehicular communications that ensure reliable safety messages dissemination in vehicular networks. In the proposed scheme, each Road Side Unit (RSU) and On-Board Units (OBU) is assigned a time slot in a fix medium access time (elementary cycle). Each RSU controls time access using the knowledge of the connected vehicles. Two realistic scenarios, Vehicle-to-Infrastructure (V2I)/Infrastructure-to-Vehicle (I2V) and Vehicle-to-Vehicle (V2V), are presented to test the proposed scheme. The proposed scheme is simulated and the presented results validate its effectiveness in terms of higher safety packets success rate and low communications delays.